Stability assessment of polyvinyl-ether-based TiO2, SiO2 and their hybrid nanolubricants - Mohd Farid, Ismail; Wan Azmi, Wan Hamzah; Rizalman, Mamat; Sharma, Korada Viswanatha; Nurul Nadia, Mohd Zawawi (MDPI, 2023)
Poor characterisation of nanoparticle suspensions impedes the development of nanolubricants for use in refrigeration and air-conditioning systems. Chemical treatment techniques, such as surfactants, are inappropriate for enhancing the stability of nanolubricants intended for use in vapour-compression refrigeration (VCR) systems. Prior to incorporating nanolubricants into the system, the stability of TiO2 and SiO2 nanoparticles dispersed in PVE was therefore investigated. The nanolubricants were prepared by a two-step method with the aid of an ultrasonication bath homogeniser. Visual observation and ultraviolet–visible (UV–Vis) spectrophotometric analysis were used, and zeta potential analysis was then performed to confirm the nanolubricants’ stability condition. The TiO2/PVE nanolubricant was observed to be maintained at a 95% concentration ratio for up to 30 days of evaluation. The TiO2/PVE, SiO2/PVE, and SiO2-TiO2/PVE exhibited zeta potential values of 203.1 mV, 224.2 mV, and 105.3 mV, respectively, after 7 h of sonication. A high absolute value of zeta potential indicates that the electrostatic repulsive forces between nanoparticles are exceptionally strong, indicating an excellent stable suspension. The high values of zeta potentials validated the excellent stability conditions determined by UV–Vis analysis and visual observation. It can be concluded that ultrasonication times of 7 h produced the most stable state for mono- and hybrid nanolubricants.